Accounting for failure: risk-based regulation and the problems of ensuring healthcare quality in the NHS. (18th May 2016) - Beaussier, Anne-Laure; Demeritt, David; Griffiths, Alex; Rothstein, Henry
Abstract : In this paper, we examine why risk-based policy instruments have failed to improve the proportionality, effectiveness, and legitimacy of healthcare quality regulation in the National Health Service (NHS) in England. Rather than trying to prevent all possible harms, risk-based approaches promise to rationalise and manage the inevitable limits of what regulation can hope to achieve by focusing regulatory standard-setting and enforcement activity on the highest priority risks, as determined through formal assessments of their probability and consequences. As such, risk-based approaches have been enthusiastically adopted by healthcare quality regulators over the last decade. However, by drawing on historical policy analysis and in-depth interviews with 15 high-level UK informants in 2013–2015, we identify a series of practical problems in using risk-based policy instruments for defining, assessing, and ensuring compliance with healthcare quality standards. Based on our analysis, we go on to consider why, despite a succession of failures, healthcare regulators remain committed to developing and using risk-based approaches. We conclude by identifying several preconditions for successful risk-based regulation: goals must be clear and trade-offs between them amenable to agreement; regulators must be able to reliably assess the probability and consequences of adverse outcomes; regulators must have a range of enforcement tools that can be deployed in proportion to risk; and there must be political tolerance for adverse outcomes.